Innovative approach for modelling gravity-induced signal path variations of VLBI radio telescopes - Michael Lösler; Cornelia Eschelbach; Ansgar Greiwe; Boye Zhou; Lucia McCallum (Earth, Planets and Space)
Abstract Gravitationally induced deformation of the receiving unit of radio telescopes used for Very Long Baseline Interferometry (VLBI) distorts the observations and biases the deduced products. As this deformation acts systematically and is individual for each radio telescope, the International VLBI Service for Geodesy and Astrometry (IVS) calls for gravitational deformation investigations to be able to correct VLBI data on the observation level. The most commonly used approach for modelling signal path variations was developed in 1988 during investigations at the 26-m VLBI radio telescope in Fairbanks (Alaska). This approach considers only homologous deformation of the receiving unit and takes into account three main deformation patterns affecting the signal path. For this reason, the measuring and modelling effort can be greatly simplified because the original spatial problem is reduced to a two-dimensional problem. However, more recent investigations refute the assumption of homogeneous deformation, because the receiver unit can be affected by arbitrary deformation patterns. Hence, identification and modelling as well as considering all deformation patterns that can be parameterised in a corresponding correction function require specific and more complex analysis approaches. In this contribution an innovative approach for modelling signal path variations is presented, based on Zernike polynomials. In contrast to the conventional approach, the proposed approach models the entire receiving unit spatially, and is not restricted to a homologous deformation pattern. This new approach has been successfully exercised on the 26-m radio telescope at the Mount Pleasant Radio Observatory Hobart (Tasmania, Australia). Despite the large dimensions of this radio telescope, the detected deformation is unexpectedly small, and leads to signal path variations of less than 2 mm. Graphical Abstract